Occurrence of Ochratoxin A in Nigeria ready for sale cocoa beans - Dongo, L.; Bandyopadhyay, Ranajit; Kumar, M.; Ojiambo, P.S. (2008)
Ochratoxin A (OTA) is a mycotoxin commonly associated with many food and beverage crops grown in tropical and temperate regions. There is no data available regarding OTA contamination of ready for sale cocoa beans in Nigeria. The objective of this study was to assess the levels of OTA contaminations in ready for sale cocoa bean samples collected from farmers during a survey in three states of Nigeria. An indirect competitive ELISA protocol was used to quantify OTA levels in the samples. Out of 59 samples analyzed, >90% were positive for OTA, with concentrations ranging from 1.0 to 277.5 pg kg". Cocoa bean samples from Cross Rivers State were more contaminated in terms of OTA levels, the higher concentrations observed was277.5 and 200.8 pg kg" in 2 samples from Cross Rivers and Edo States, respectively. However, There were no significant differences among the OTA levels of the three States (p > 0.05).